Effects Of Transformational Leadership, Training, And Job Satisfaction On Employee Performance With Organizational Commitment As A Between Variable - Yusuf Ronny Edward; Kuras Purba (Jurnal Manajemen Industri dan Logistik, 2024)
This study aims to determine and analyze the effects of transformational leadership, training, and job satisfaction on employee performance through organizational commitment at PT Asia Mulia Transpacific. This study uses a quantitative associative method with structural equation modeling. The collect data from the variables of transformational leadership, training, job satisfaction, organizational commitment, and employee performance. The sampling technique used is proportional stratified random sampling using the Slovin formula. Based on SEM analysis, transformational leadership, training, and job satisfaction positively and significantly impact employee performance through organizational commitment. The contribution of transformational leadership, training, job satisfaction, and organizational commitment variables together in shaping employee performance is 74.7%. The rest, as much as 25.3%, is explained by other variables outside the study.